Description of two new species of Xevioso (Araneae: Phyxelididae) from Southern Africa, with the northernmost localities for the genus - Pett, Brogan L.; Jocqué, Rudy (European Journal of Taxonomy, 2020)
Two new species of Phyxelididae are described from southern Africa: Xevioso cepfi sp. nov. (♂♀), from mountains in the Niassa Province of northern Mozambique, and X. megcummingae sp. nov. (♂♀), from urban Harare, northern Zimbabwe and the Viphya Mts in Malawi. They represent the northernmost localities of the genus. An identification key, partially adapted for the new species, is presented. The biogeographical importance of the mountain areas on both sides of the northern part of Lake Malawi is discussed.